EFFORTS TO IMPROVE LEARNING OUTCOMES OF PASSING IN SOCCER GAMES THROUGH THE COMMAND TEACHING STYLE IN CLASS III STUDENTS OF AL WASLIYAH ELEMENTARY SCHOOL 25 MARELAN MEDAN ACADEMIC YEAR 2019/2020 - Fajar Mugo Raharjo (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
The purpose of this study is to improve student learning outcomes in the Physical Education subject especially in passing material by using the command teaching style in third grade elementary school students. Al Wasliyah 25 Marelan. This research method is classroom action research and research subjects are classes that have certain problems. The class studied consisted of 26 students. The instruments used in this study were learning outcomes tests and observation sheets. From the results of research conducted, seen an increase in the first cycle of 57.69%, then increased to 88.46% in the second cycle. From the analysis of the data it can also be seen that the student learning outcomes of the learning outcomes test before using the command teaching style is still very low. Passing learning is complete after the second cycle, this is due to the provision of motivation that triggers students' enthusiasm for learning and changes in learning variations. While in cycle I, students are not accustomed to the teaching methods provided by researchers, so students need to adapt to the learning methods provided by researchers. Based on the results of the research above, it can be concluded that student learning outcomes by utilizing the command teaching method in grade III elementary school. Al Wasliyah 25 Marelan Academic Year 2019/2020 has increased from cycle I to cycle II